2019
DOI: 10.1152/ajplung.00415.2018
|View full text |Cite
|
Sign up to set email alerts
|

Resolvin D1 attenuates mechanical stretch-induced pulmonary fibrosis via epithelial-mesenchymal transition

Abstract: Mechanical ventilation-induced pulmonary fibrosis plays an important role in the high mortality rate of acute respiratory distress syndrome (ARDS). Resolvin D1 (RvD1) displays potent proresolving activities. Epithelial-mesenchymal transition (EMT) has been proved to be an important pathological feature of lung fibrosis. This study aimed to investigate whether RvD1 can attenuate mechanical ventilation-induced lung fibrosis. Human lung epithelial (BEAS-2B) cells were pretreated with RvD1 for 30 min and exposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 41 publications
0
24
1
1
Order By: Relevance
“…Significant EMT has been demonstrated in the airway epithelial cells of patients with cOPd (14)(15)(16), and EMT has been suggested as an important factor for airway remodeling in cOPd (17,18). Previous studies have demonstrated that primary airway epithelial cells subjected to mechanical stretch acquire EMT phenotypes (19)(20)(21). However, the specific molecular mechanisms of EMT in response to mechanical stress remain poorly understood.…”
Section: Transient Receptor Potential Canonical 1 Channel Mediates Thmentioning
confidence: 99%
“…Significant EMT has been demonstrated in the airway epithelial cells of patients with cOPd (14)(15)(16), and EMT has been suggested as an important factor for airway remodeling in cOPd (17,18). Previous studies have demonstrated that primary airway epithelial cells subjected to mechanical stretch acquire EMT phenotypes (19)(20)(21). However, the specific molecular mechanisms of EMT in response to mechanical stress remain poorly understood.…”
Section: Transient Receptor Potential Canonical 1 Channel Mediates Thmentioning
confidence: 99%
“…It is in accordance with a study from Zeng et al, showing that DHA inhibits TGF-β-induced rat renal fibroblast activation at a dose and time-dependent manner [ 85 ]. DHA derivative such as resolvin D1 was also evaluated in extra-intestinal fibrosis model [ 86 ]. Resolvin D1 treatment was able to reduce mechanical stretch-induced EMT and SMAD signaling in a murine model of lung fibrosis [ 86 ].…”
Section: Beneficial Effects Of Dietary Componentsmentioning
confidence: 99%
“…Maresins have organ protective effects, decrease edema, improve lung mechanics and tissue hypoxia (75). RvD1 decreases pulmonary edema, leukocyte infiltration and the release of pro-inflammatory cytokines and alleviates lung injury (76)(77)(78)(79) and RvE1 can restore mitochondrial function in human alveolar epithelial cells and accelerates the resolution of experimental lung inflammation (80)(81)(82). Moreover, protectin D1 has beneficial effects in influenza-infected mice (83) and 15-epiLXA4 inhibits neutrophil infiltration and enhances pathogen clearance (84,85).…”
Section: Acute Respiratory Distress Syndrome (Ards)mentioning
confidence: 99%